Cotton dust, endotoxin and cancer mortality among the Shanghai textile workers cohort: a 30-year analysis. Issue 10 (4th July 2013) - Fang, S C; Mehta, A J; Hang, J Q; Eisen, E A; Dai, H L; Zhang, H X; Su, L; Christiani, D C
Abstract : Background: Although occupational exposure to cotton dust and endotoxin is associated with adverse respiratory health, associations with cancer are unclear. We investigated cancer mortality in relation to cotton dust and endotoxin exposure in the Shanghai textile workers cohort. Methods: We followed 444 cotton textile and a reference group of 467 unexposed silk workers for 30 years (26 777 person-years). HRs for all cancers combined (with and without lung cancer) and gastrointestinal cancer were estimated in Cox regression models as functions of cotton textile work and categories of cumulative exposure (low, medium, high), after adjustment for covariates including pack-years smoked. Different lag years accounted for disease latency. Results: Risks of mortality from gastrointestinal cancers and all cancers combined, with the exclusion of lung cancer, were increased in cotton workers relative to silk workers. When stratified by category of cumulative cotton exposure, in general, risks were greatest for 20-year lagged medium exposure (all cancers HR=2.7 (95% CI 1.4 to 5.2); cancer excluding lung cancer HR=3.4 (1.7–7.0); gastrointestinal cancer HR=4.1 (1.8–9.7)). With the exclusion of lung cancer, risks of cancer were more pronounced. When stratified by category of cumulative endotoxin exposure, consistent associations were not observed for all cancers combined. However, excluding lung cancer, medium endotoxin exposure was associated with all cancers and gastrointestinal cancer in almost all lag models. Conclusions: Cotton dust may be associated with cancer mortality, especially gastrointestinal cancer, and endotoxin may play a causative role. Findings also indirectly support a protective effect of endotoxin on lung cancer.